RECENT ADVANCES IN ART APPLICATION IN NIGERIA. A FIELD PERSPECTIVE - Olorunleke, Solomon (Translational Research in Veterinary Science, 2023)
In recent times, assisted reproductive technologies have emerged and started to replace the conventional techniques in Nigeria. It is noteworthy that for sustainable livestock production, it is very important to adopt the use of these Assisted Reproductive technologies. These assisted reproductive technologies, in male and female is revolutionizing Livestock production in Nigeria in Cattle, Goat, Sheep, Swine, Equine, Poultry, Rabbit etc. production. The present review is aimed at collating the experiences of Real People Concept and its collaborators on the various assisted reproductive projects carried out directly and indirectly. These includes Oestrus synchronization, Artificial insemination, Follicular dynamic, Ultrasonography, Ultrasonic pregnancy detection, Pregnancy diagnosis, hormonal Assay, Heat detection, Vagina Electrical measurement, Semen collection, Semen evaluation, Semen extending, semen processing, Semen freezing, and semen storage. This review shows that these assisted reproductive technologies are being currently applied in the livestock industry in Nigeria with acceptable results. On the other hand, a lot has to be done in the use and application of the technologies in Nigeria for improved livestock production.